The mark of the king [large type] - Green, Jocelyn (Center Point Large Print, 2017)
"Unjustly imprisoned for the death of her client, midwife Julianne Chevalier is exiled to the French colony of Louisiana in 1720. She marries a fellow convict in order to sail, but when tragedy strikes--and a mystery unfolds--Julianne must find her own way in this dangerous land while bearing the brand of a criminal"--